PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE STUDENT TEAMS ACHIVEMENT DIVISION (STAD) UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS IV SD NEGERI 15 AIR JAMBAN - Mashita Sri Handayani Sri Handayani; Sehatta Saragih Saragih; Jalinus ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract:This reseacrh based on the students math ability class IV SD Negeri 15 Air Jamban under Minimum Mastery Criteria with a percentage of 42% and the learning process still teacher center. The research was classroom action research. This research aims to outcomes students by implementing cooperative learning model structural approach of Numbered Heads Together. The subject of the research is students of class IV SD Negeri 15 Air Jamban in the second semester academic years 2013/2014. There are 24 students in the class, consisting 13 girls and 11 boys. The instrument of data collection on this research are observation sheets and math achievement tests. The observation sheets are analyze in qualitative descriptive way, while the math achievement tests are analyze in quantitative descriptive way. The qualitative analysis showed an improvement of learning process prior to the action of the first cycle to the second cycle. Then the result of this research showed an increase in students from the base score with the percentage 42% to 56,5 % on the first daily test and 95,8% on the second daily test. From the results of this study concluded that Cooperative Learning model Student Teams Achivement Devision can improve the math achievement of students at class IV SD Negeri 15 Air Jamban in the second semester academic years 2013/2014. Key Word : Mathematics Learning Outcome, Cooperative Learning Type STAD.